Improving awareness, knowledge and awareness with epilepsy educational programme for Malaysian parents of children with epilepsy / Seet Yee Hong - Seet , Yee Hong (2017)
Introduction: Good awareness, knowledge and attitudes of parents of children with epilepsy (CWE) is important in enabling CWE to lead a normal life with epilepsy. The interactive animated epilepsy education programme (IAEEP) is a potential effective epilepsy educational tool that can help improve awareness, knowledge, attitude (AKA) of parents of CWA.